528. Coronavirus Disease 2019 in Children Cared for at Texas Children's Hospital: Implications of Repeat Testing on Infection Control Strategies. (31st December 2020) - Foster, Catherine; Marquez, Lucila; Koy, Tjin; Singh, Ila; Campbell, Judith
Abstract: Background: Accurate diagnosis of coronavirus disease 2019 (COVID-19) is key for source control and interrupting disease transmission. To better understand the length of viral shedding in children and potential infection control implications, we describe 51 children with COVID-19 who underwent repeat testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at Texas Children's Hospital (TCH). Methods: We performed a retrospective chart review of all pediatric patients (< 21 years of age) with ≥ 2 nasopharyngeal specimens tested for SARS-CoV-2 by reverse transcription-polymerase chain reaction (rt-PCR) and at least one positive result between 3/13/2020 and 6/7/2020 through the TCH Molecular Microbiology Laboratory. Results: Fifty-one patients met inclusion criteria. The median age was 8.6 years (0.02–19.2 years). Sixteen (31%) children were hospitalized. Fourteen (27%) patients underwent testing for surveillance purposes (including 3 admitted patients). Two SARS-CoV-2 tests were performed in 25 (49%) children; while 12 (24%) children had 3 tests, 4 (8%) children had 4 tests, and 10 (20%) children had ≥ 5 tests (including 1 patient with underlying malignancy who had 9 SARS-CoV-2 PCRs performed). SARS-CoV-2 testing timeline for 9 hospitalized children is shown (Fig 1). The median time between collection of tests 1 and 2 was 14 days (n=51, range 1, 53 days). For children with conversion (first detected to first not-detected sample), the median time was 15 days (n=31, range 1, 45 days). For patients with consecutive positive SARS-CoV-2 PCRs, the median time of positivity was 10 days (n=19, range 2, 31). One patient with malignancy had 5 tests over 6 weeks in the outpatient setting and each time alternated between detected and not-detected. Following diagnosis with COVID-19, one patient with sickle cell disease likely had re-infection and had a positive test after having 2 consecutive negative tests; his last SARS-CoV-2 rt-PCR was positive 68 days after initial positive. Fig 1. Timing of Repeat SARS-CoV-2 PCRs in Select Hospitalized Children with COVID-19 Conclusion: We observed variation in the duration of SARS-CoV-2 rt-PCR positivity in children with COVID-19. For children with COVID-19, a single negative molecular assay for SARS-CoV-2 may not be predictive of sustained negativity. Disclosures: All Authors : No reported disclosures